New Record of the Egg-larval Parasitoid, Chelonus formosanus Sonan of Fall Armyworm, Spodoptera frugiperda (J.E. Smith) in the Philippines - Orlando Adona Calcetas; Ravindra Chandra Joshi; Ankita Gupta; Avinjikkattu Parambil Ranjith; Mary Ann Madrid; Joash Fameronag (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2023)
The egg-larval parasitoid on fall armyworm (FAW), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) have not reported in the Philippines. This paper summarizes the global biological information on two species of Chelonus and their role in the regulation of FAW. The FAW egg masses and larvae were collected in the corn plantations inside the Lipa Agricultural Research Station, Marawoy, Lipa City, Batangas. The collected egg masses and larvae were reared at the Entomology Laboratory of the Department of Agriculture-Regional Crop Protection Center IVA. The larvae of FAW were observed for the emergence of parasitoids. Two cocoons of the parasitoid from the rearing cages were obtained for species determination. Three adults from the emerged parasitoids, each male and female, were initially preserved and labeled. Color images of habitus and other morphological characters of the parasitoid were taken using a DSLR camera attached to an Olympus SZ61-60 microscope. This research found two species that emerged from FAW: Chelonus formosanus and the new record of C. semihyalinus. We also highlight the need for more research in the Philippines on exploring the diversity of indigenous natural enemies, the development of mass-rearing techniques, and their utilization to manage fall armyworms.